Sea-Ice Morphology Change in the Canada Basin Summer: 2006–2015 Ship Observations Compared to Observations From the 1960s to the Early 1990s - Hutchings, Jennifer K.; Faber, M. Kate (Frontiers in Earth Science, 2018)
An ice watch, encompassing visual observation of sea ice conducted from the ship’s bridge, is typically performed on sea-ice oriented research cruises. Ice watch data collected during a decade, 2006-2015, of annual cruises to the Beaufort Sea and Canadian Basin characterizes sea-ice morphology during mid to late summer. Observations not otherwise available on extensive regional scales with remote sensing are highlighted, including stage of melt, floe size and surface topography in summer. The summer ice pack in the Canada Basin is found to be of smaller floe size than found in 1973-1975. A disintegrating ice pack of mainly small floe size covered much on the Canada Basin in 2006-2009 and 2011-2012. Since 2007 the ice in the Canada Basin has experienced more extensive melt, and more advanced stages of melt than in 1973-1975, during the Arctic Ice Dynamics Joint Experiment (AIDJEX), and early 1990s. Since 2007, Summer ridge sail heights are lower and ridges less extensive compared to the AIDJEX period.